Diseño de revestidores y cementación del pozo x5-d del oriente ecuatoriano - Salas Hurtado, Vilma Leonela (2009)
This work presents an alternative to casing desing and volumes calculate in the ESPOL X5-D wel cementation wel cementation program, making a comparison between current desing and suggested desing